A Constitutional Court Decision Has Final Law And Binding Related to Decision No. 57/PHP.BUP-XIX/2021, North Halmahera Election Results Disputes - Laritmas , Selfianus; Gede Yusa, I; Gede Rudy, Dewa; Rosidi , Ahmad (International Journal of Educational Research & Social Sciences, 2022)
Constitutional Court Decision(MK) who is final and binding as stated in Article 24 C paragraph (1) of the 1945 Constitution of the Republic of Indonesia, and Saccording to the provisions of article 47,and explanation of article 10 paragraph (1), Law no. 24 year 2003. The final nature of this Constitutional Court decision includes binding legal force (final and binding).. It turns out, in amarConstitutional Court Decision No 57/PHP.BUP-XIX/2021 cause new legal problems or conflicts of norm because it does not yet have final and binding power in the North Halmahera election dispute, because the Constitutional Court's decision still opens the opportunity for new applications to be resubmitted in the Constitutional Court. MKNumber 14/PHP.BUP-XV/2017, and Decision Number 42/PHP.BUP-XV/2017, on amarthe decision is very clear, the decision has binding power after the decision so that the Constitutional Court can no longer re-hear the election results case after the PSU has been carried out, only the determination is carried out after the KPUD reports the PSU results.This study aims to analyze, first,Is the Constitutional Court's decision no longer final and binding in dealing with regional election disputes, especially the North Halmahera regional election dispute, second, how are the legal problems of the Constitutional Court's decision which is no longer final and binding?. This research is qualified into normative legal research, with an approach Legal approach (Statute Approach), Concept Approach and Case approach. The results of the study show, firstly, that the Constitutional Court's decision creates new legal problems in its decisions which are different from the previous decisions, Second, there is a need for Consistency of the Constitutional Court in deciding disputes that are final and binding so that it does not cause new problems in constitutional law